Structures and Corresponding Functions of Five Types of Picornaviral 2A Proteins - Yang, Xiaoyao; Cheng, Anchun; Wang, Mingshu; Jia, Renyong; Sun, Kunfeng; Pan, Kangcheng; Yang, Qiao; Wu, Ying; Zhu, Dekang; Chen, Shun; Liu, Mafeng; Zhao, Xin-Xin; et al. (Frontiers in Microbiology, 2017)
Among the few nonstructural proteins encoded by the picornaviral genome, the 2A protein is particularly special, irrespective of structure or function. During the evolution of the Picornaviridae family, the 2A protein has been highly non-conserved. We believe that the 2A protein in this family can be classified into at least five distinct types according to previous studies. These five types are (A) chymotrypsin-like 2A, (B) Parechovirus-like 2A, (C) hepatitis-A-virus-like 2A, (D) Aphthovirus-like 2A, and (E) 2A sequence of the genus Cardiovirus. We carried out a phylogenetic analysis and found that there was almost no homology between each type. Subsequently, we aligned the sequences within each type and found that the functional motifs in each type are highly conserved. These different motifs perform different functions. Therefore, in this review, we introduce the structures and functions of these five types of 2As separately. Based on the structures and functions, we provide suggestions to combat picornaviruses. The complexity and diversity of the 2A protein has caused great difficulties in functional and antiviral research. In this review, researchers can find useful information on the 2A protein and thus conduct improved antiviral research.